Bank Risk-Taking Behavior during a Prolonged Low Interest Rate Era: The Case of Thailand - Charnvitayapong, Kovit (Journal of Applied Economics and Management Strategy, 2020)
ABSTRACT The objective of this study was to investigate the impact of prolonged expansionary monetary policy upon bank risks in Thailand. The data comprised balance sheets for 19 commercial banks from the first quarter of 2001 to the first quarter of 2019. The study hypothesized that prolonged low interest rates could impact the bank sources of liability-side funding, leading to leverage, and that different-sized banks may react differently. The results from a two-stage procedure showed that banks may borrow more to invest in risky projects if investment sensitivity to leverage has an inverse relationship with the prolonged low interest rate. This study used a fixed effects model to compare three risk proxies and justified the usage of leverage as a risk measure. These findings indicated that small- and medium-sized banks tended to take more risks than large banks. The final section used quantile regression to analyze the interest rate impact and other variables upon different levels of bank risks. The results indicated that different-sized banks responded differently to various variables under low-interest rate conditions. Keywords: prolonged low interest rate, leverage, risk, two-stage procedure, quantile regression